2013
DOI: 10.1007/s00535-013-0752-y
|View full text |Cite
|
Sign up to set email alerts
|

Potent inhibitory effect of alcoholic beverages upon gastrointestinal passage of food and gallbladder emptying

Abstract: Background and aimsCurrent knowledge about the effect of alcoholic beverages on postprandial functioning of the digestive system is scarce and inconsistent. This study addresses their influence upon meal movement along the gut and meal-induced gallbladder emptying.MethodsThree examination blocks involved each 12 healthy volunteers. Ingestion of a solid 1485 kJ meal was followed by intake of 400 ml beer (4.7 %vol), 200 ml red wine (13.7 %vol) or 100 ml whisky (43.5 %vol) or matching volumes of control fluids. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Both GIP and GLP-1 responses to ingested glucose depend on the glucose load, such that higher rates of glucose entry into the duodenum induce greater incretin secretion [24]. Although we do not know the reason for the greater rate of increase of plasma glucose, it seems unlikely that it is related to gastric emptying, because alcohol has been consistently shown to inhibit the rate of gastric emptying of both liquid and solid food [25][26][27]. Finally, it must be noted that an enhanced insulin response after pretreatment with alcohol can be elicited via intravenous infusion of glucose, which bypasses the stimulus for GIP and GLP-1 secretion [14,15,17].…”
Section: Wine-induced Change In Gip Iauc (%)mentioning
confidence: 98%
“…Both GIP and GLP-1 responses to ingested glucose depend on the glucose load, such that higher rates of glucose entry into the duodenum induce greater incretin secretion [24]. Although we do not know the reason for the greater rate of increase of plasma glucose, it seems unlikely that it is related to gastric emptying, because alcohol has been consistently shown to inhibit the rate of gastric emptying of both liquid and solid food [25][26][27]. Finally, it must be noted that an enhanced insulin response after pretreatment with alcohol can be elicited via intravenous infusion of glucose, which bypasses the stimulus for GIP and GLP-1 secretion [14,15,17].…”
Section: Wine-induced Change In Gip Iauc (%)mentioning
confidence: 98%
“…whisky has around 40% v/v (ref. 25 ), the same is true for ethanol in tequila 26 , and the typical rum has around 40% (ref. 27 ).…”
Section: Production and Use Of The Alcoholsmentioning
confidence: 70%
“…The American pharmacologist Tyler suggested that for aperitifs it was the alcohol rather than the tastants which were responsible for any improvements in digestion [ 13 ]. While various alcoholic beverages do delay gastric emptying [ 39 41 ], including aperitifs [ 42 , 43 ], the amount of alcohol found in a single dose of bitters made from either fluid extracts or tinctures is minimal (0.5–1.5 mL) and unlikely to affect gastric emptying.…”
Section: Theories Of Bitter Activitymentioning
confidence: 99%